Response of cytokinins and nitrogen metabolism in the fronds of Pteris sp. under arsenic stress - Pavlíková, Daniela; Zemanová, Veronika; Pavlík, Milan; Dobrev, Petre I; Hnilička, František; Motyka, Václav (PloS one, 2020)
Given the close relationship between cytokinins (CKs), photosynthesis and nitrogen metabolism, this study assessed the effect of arsenic (As) contamination on these metabolic components in the As-hyperaccumulators Pteris cretica L. var. Albo-lineata (Pc-A) and var. Parkerii (Pc-P) as well as the As-non-hyperaccumulator Pteris straminea Mett. ex Baker (Ps). The ferns were cultivated in a pot experiment for 23 weeks in soil spiked with As at the levels 20 and 100 mg·kg-1. For the purpose of this study, the CKs were placed into five functionally different groups according to their structure and physiological roles: bioactive forms (bCKs; CK free bases); inactive or weakly active forms (dCKs; CK N-glucosides); transport forms (tCKs; CK ribosides); storage forms (sCKs; O-glucosides); and primary products of CK biosynthesis (ppbCKs; CK nucleotides). An important finding was higher CKs total content, accumulation of sCKs and reduction of dCKs in As-hyperaccumulators in contrast to non-hyperaccumulator ferns. A significant depletion of C resources was confirmed in ferns, especially Ps, which was determined by measuring the photosynthetic rate and chlorophyll fluorescence. A fluorescence decrease signified a reduction in the C/N ratio, inducing an increase of bioactive CKs forms in Pc-P and Ps. The impact of As on N utilization was significant in As-hyperaccumulators. The glutamic acid/glutamine ratio, an indicator of primary N assimilation, diminished in all ferns with increased As level in the soil. In conclusion, the results indicate a large phenotypic diversity of Pteris species to As and suggest that the CKs composition and the glutamic acid/glutamine ratio can be used as a tool to diagnose As stress in plants.
Keywords: biomasa; Amino Acids; látky znečišťující půdu; Plant Leaves; Arsenic; cytokininy; aminokyseliny; Cytokinins; arsen; Photosynthesis; dusík; Soil Pollutants; Pteris; Biomass; Nitrogen; listy rostlin; fotosyntéza